Assessment of Polar Ionospheric Observations by VIPIR/Dynasonde at Jang Bogo Station, Antarctica: Part 1—Ionospheric Densities - Eunsol Kim; Geonhwa Jee; Young-Bae Ham; Nikolay Zabotin; Changsup Lee; Hyuck-Jin Kwon; Junseok Hong; Jeong-Han Kim; Terence Bullett (Remote Sensing, 2022)
Vertical incidence pulsed ionospheric radar (VIPIR) has been operated to observe the polar ionosphere with Dynasonde analysis software at Jang Bogo Station (JBS), Antarctica, since 2017. The JBS-VIPIR-Dynasonde (JVD) provides ionospheric parameters such as the height profile of electron density with NmF2 and hmF2, the ion drift, and the ionospheric tilt in the bottomside ionosphere. The JBS (74.6°S, 164.2°E) is located in the polar cap, cusp, or auroral region depending on the geomagnetic activity and local time. In the present study, an initial assessment of JVD ionospheric densities is attempted by the comparison with GPS TEC measurements which are simultaneously obtained from the GPS receiver at JBS during the solar minimum period from 2017 to 2019. It is found that the JVD NmF2 and bottomside TEC (bTEC) show a generally good correlation with GPS TEC for geomagnetically quiet conditions. However, the bTEC seems to be less correlated with the GPS TEC with slightly larger spreads especially during the daytime and in summer, which seems to be associated with the characteristics of the polar ionosphere such as energetic particle precipitations and large density irregularities. It is also found that the Dynasonde analysis seems to show some limitations to handle these characteristics of the polar ionosphere and needs to be improved to produce more accurate ionospheric density profiles especially during disturbed conditions.